Fiscal adjustments and income inequality: a first assessment - Agnello, Luca (2012)
Using a statistical approach to identify fiscal adjustments, we find that fiscal consolidation appears to shorten the income gap. Fiscal austerity plans that succeed in bringing public debt to a sustainable path seem to be more likely to reduce inequality. Expansionary fiscal adjustments are particularly important to promote changes in the income distribution.